2018
DOI: 10.1186/s12893-018-0335-1
|View full text |Cite
|
Sign up to set email alerts
|

Aortoesophageal fistula and arch pseudoaneurysm after removing of a swallowed chicken bone: a case report of one-stage hybrid treatment

Abstract: BackgroundAortoesophageal fistula (AEF) and arch pseudoaneurysm are rare complications induced by a foreign body, and considerable controversy remains regarding the appropriate management strategies. We herein report a successful one-stage hybrid treatment in a patient with AEF and arch pseudoaneurysm.Case presentationThe patient, a 40-year-old man, presented to the emergency room because of intense retrosternal discomfort for 3 days and hematemesis for 3 h. The esophagoscopy and thoracic enhanced computed tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
0
8
0
3
Order By: Relevance
“…Once the symptoms of infection occur in any patient with a history of AEF, especially those without secondary surgery, they should be highly suspected for the possibility of mediastinitis or stent-graft infection and evaluated for secondary surgeries in the clinical setting. Also, lifelong imaging surveillance is mandatory [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the symptoms of infection occur in any patient with a history of AEF, especially those without secondary surgery, they should be highly suspected for the possibility of mediastinitis or stent-graft infection and evaluated for secondary surgeries in the clinical setting. Also, lifelong imaging surveillance is mandatory [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In special patients, the esophageal defects were healed by themselves. Tao et al have reported that a 5 mm esophageal fistula caused by fishbone ingestion is healed on its own after endovascular repair, but the whole process took 1 year and 3 months, another case reported by Shen JY et al with two esophageal fistulas of 0.2 cm and 0.3 cm in diameter took 6 months to heal by itself [6,7]. In most of the cases, considering the high risk of infection, most of the authors are in favor of secondary esophagectomy followed by esophageal reconstruction [1,3,8].…”
Section: Discussionmentioning
confidence: 99%
“…The most important goal of treating AEF is to prevent massive hemorrhage. According to some literature reports, TEVAR is a type of endoluminal aortic stent that was developed recently as minimally invasive therapy for AEF ( Shen et al, 2018 ; Takeno, Ishii, Nanashima, & Nakamura, 2020 ). Endovascular repair is a less invasive method, which refers to the insertion of a covered stent through the femoral arteries to fix the normal aorta above and below the aneurysm, acting as a cannula through the aneurysm sac ( Kent, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Также первичные аорто-дигестивные фистулы могут быть следствием инфекционно-воспалительного процесса [11], прорастания опухоли [12], повреждения стенки полого органа инородным телом [13], а при неизмененной аорте -осложнением дивертикулита сигмовидной кишки [14], на фоне радиационно-индуцированного хронического воспаления кишечной стенки [15] и в результате ряда других более редких причин.…”
Section: классификацияunclassified
“…Объем «открытой» операции при аорто-дигестивной фистуле зависит от общего состояния пациента, локализации и степени повреждения аорты и полого органа, тяжести местного инфекционно-воспалительного процесса [13]. При умеренном инфицировании предпочтительна реконструкция аорты in situ дакроновым или политетрафторэтиленовым трансплантатом, при этом дополнительное укрытие его прядью большого сальника является независимым предиктором выживания [7; 36].…”
Section: лечениеunclassified